Remote Sensing for Agriculture, Ecosystems, and Hydrology VII 2005
DOI: 10.1117/12.626793
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration estimation in the Brazil using NDVI data

Abstract: The purpose of this study is to analyze the monthly mean spatial and temporal distribution of evapotranspiration (ET) during the 1981-2000 period in Brazil using remotely sensed data. The methodology involves the use of a relationship between ET and Normalized Difference Vegetation Index (NDVI). ET was estimated for the main Brazilian biomes through the Penman-Monteith method using climatological data from 194 Brazilian meteorological stations during the 1961-1990 period. NDVI data for the July 1981 to July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
10
1
Order By: Relevance
“…The strong significant positive correlation between ET WV2 and ET WUCOLS (r 2 = 0.96, p > 0.05) demonstrates well the feasibility and practicality of a remotely-sensed ET estimation approach in Veale Gardens. This finding is in line with several studies that have found a strong and reliable relationship between aerial-satellite-based Landscape NDVI measurements and ground-based ET measurements [17,[53][54][55][56][57][58][59]. A significant decrease in rainfall in January 2013 imposed stress conditions to the vegetation in Veale Gardens.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The strong significant positive correlation between ET WV2 and ET WUCOLS (r 2 = 0.96, p > 0.05) demonstrates well the feasibility and practicality of a remotely-sensed ET estimation approach in Veale Gardens. This finding is in line with several studies that have found a strong and reliable relationship between aerial-satellite-based Landscape NDVI measurements and ground-based ET measurements [17,[53][54][55][56][57][58][59]. A significant decrease in rainfall in January 2013 imposed stress conditions to the vegetation in Veale Gardens.…”
Section: Discussionsupporting
confidence: 80%
“…Statistical analysis and ground measurement has confirmed that a near linear relationship can be found between VIs and photosynthesis by vegetation canopy [16]. Long-term RS data analysis by Rossato et al [17] showed that ET and NDVI have a near-linear relationship. A linear relationship between NDVI and basal crop coefficient for irrigated agricultural fields was also reported by Duchemin et al [18].…”
Section: Introductionmentioning
confidence: 78%
“…These two seasons were characterized because in the initial stage crop needs smaller water requirements, whereas in the mid-season crop needs higher water requirements, as we can see in the next section. The ET c maps created in this study are in agreement with other researchers; for example, in [2,4,58,59], they generated ET c maps using c derived from remote sensing-based vegetation indices. Other researchers reported that c derived from canopy reflectance based vegetation index had the potential to estimate crop evapotranspiration at regional and field scales, for example, in [17,18,29,55,60,61].…”
Section: 3supporting
confidence: 73%
“…NDVI has good correlation with evapotranspiration as NDVI is proportional to the vaporized water into the atmosphere [4,10]. This section deals with the relationship of NDVI with total evapotranspiration over Bangladesh through the use of interannual time series variation, spatial correlation, scatter plot and interannual correlation.…”
Section: Association Of Ndvi With Evapotranspirationmentioning
confidence: 99%